Microencapsulation of pineapple peel extract by spray drying using maltodextrin, inulin, and arabic gum as wall matrices - Lourenço, Sofia C. (2020)
A pineapple peel hydroalcoholic extract rich in phenolic compounds, was stabilized by microencapsulation using spray drying technology, with maltodextrin, inulin, and arabic gum as wall materials. The influence of the type of wall material and drying temperature (150 and 190 C) on the particles properties was studied. The particles presented a spherical shape with a diameter ranging from approximately 1.3 to 18.2 um, the exception being the ones with inulin that showed a large degree of agglomeration. All powders produced presented an intermediate cohesiveness and a fair to good flowability according to Carr index and Hausner ratio, which envisages suitable handling properties at an industrial scale. The microencapsulation processes using maltodextrin and arabic gum at 150 ºC were the ones that showed higher maintenance of the antioxidant activity of compounds present in the extract before encapsulation during spray drying. In addition, the microparticles obtained were quite effcient in stabilizing the encapsulated phenolic compounds, as their antioxidant activity did not change significantly during six months of storage at 5 ºC